Determination of strategies used for the prevention of mosquito bites - Thapa, Raj Kumar (Journal of Nepal Health Research Council, 2025)
Background: Vector borne diseases are one of the prevailing global healthcare problems caused by mosquito bites. The main objective of this study was to determine the strategies used for the prevention of mosquito bites by general public of Kaski district, a mosquito bite prone area of Western Nepal, as evidenced by rising dengue cases. Methods: A cross-sectional study with 435 households were surveyed, for the strategies used for mosquito bite prevention, in representative 15 wards of one metropolitan and four rural municipalities of Kaski district, selected by simple random sampling technique. The survey was conducted during a period of November, 2022 – February, 2023. Data was analyzed using Statistical Package for Social Science (SPSS). Results: Approximately 4% of study participants used traditional methods such as smoke from burnt medicinal plants, burnt clothes and grass, and the application of mustard oil for the prevention of mosquito bites. Majority (92%) of participants used non-traditional methods like mosquito net, mosquito incense, mosquito bat and mosquito repellent for the prevention of mosquito bites. Only 13% of study participants used some kind of personal use mosquito repellent; cream being the most commonly used one. Age, ethnicity, residence, education and income were found to be significantly associated with the use of mosquito bite prevention strategy. Majority of the respondents were unaware of the governmental plans and their implementation for mosquito control and bite prevention strategies. Conclusion: This study summarises the strategies used for the prevention of mosquito bites by the residents of Kaski district of Nepal. Future interventional studies are warranted to enhance the awareness about the effective strategies for the prevention of mosquito bites. Keywords: Kaski; mosquito bite; Nepal; prevention strategies; vector borne disease.